METHODOLOGY FOR JUSTIFYING THE DERIVATIVE PROCEDURE FOR FORMING THE NATIONAL GUARD OF UKRAINE FOR LONG-DISTANCE MARCHES IN TIMES OF WAR - Zhabinskyi, Volodymyr; Makhobei, Andrii; Podviaznikov, Serhii (Honor and Law, 2025)
The article analyzes the current experience gained by the formations of the National Guard of Ukraine and substantiates modern approaches to solving the tasks of building the marching order of NGU formations for long-distance marches. A methodology for building the marching order of NGU formations for long distances is proposed. The procedure for the commander and staff of the National Guard of Ukraine formation to organize the march is considered. It is concluded that the marching order of the NGU formation for long-distance marches is established depending on the conditions of the situation. It is noted that in order to increase the capability of the formation during movement, it is necessary to fully utilize unmanned aerial vehicle units.